A Paradigm for Development and Promulgation of a Global Code of Marketing Ethics - Rallapalli, Kumar C. (Journal of business ethics, 1999)
This paper provides a paradigm for evaluating the factors that affect the development of a global code of ethics in marketing. Based on a review of the literature pertaining to global codes of ethics, we examined the potential for the development and acceptance of a universal code of ethics in the international marketing arena. Towards that end, we suggest that any global code of ethics in marketing should consider two levels – normative guidelines and specific behaviors. A discussion detailing the factors that can impede the development of such a two-tiered code is included as well. Those factors being moral reasoning, organizational ethical climate, level of economic development and cultural dimensions. Finally, the feasibility and the possible outcomes of a global code of ethics in marketing is examined.